Non-Tariff Trade Policy in the Context of Deep Trade Integration: An Ex-Post Gravity Model Application to the EU-South Korea Agreement - Julia Grübler; Oliver Reiter (East Asian Economic Review (EAER), 2021)
Many different approaches and databases have been developed for the evaluation of nontariff measures (NTMs) and free trade agreements (FTAs). This paper is devoted to the EUSouth Korea agreement, which is the first second-generation'FTA of the EU, addressing a wide array of non-tariff policies. We review the evolution of NTM types applicable to the EU-South Korea trade relationship and the role of NTMs in ex-ante and ex-post analyses of the agreement. Subsequently a structural gravity model is employed to assess the value added of information on different aspects of FTAs and types of NTMs by evaluating their ability to predict the trade effects of the EU-South Korea FTA. Our results show that, when accounting for information on the components common in modern deep trade agreements, no additional trade effect is attributable to the EU-South Korea FTA. The evolution of NTMs differs considerably across indicators used, but trade predictions are hardly affected. Most specifications point towards a negative effect of bilateral differences in the number of technical barriers to trade (TBT) applied and sanitary and phytosanitary measures (SPS) against which trading partners issued complaints at the WTO.
Keywords: C54; F13; F14; 330; Trade Policy; Free Trade Agreement; EU; South Korea; Gravity Model